The International Space Station Environment Triggers Molecular Responses in Aspergillus niger - Blachowicz, Adriana; Romsdahl, Jillian; Chiang, Abby J.; Masonjones, Sawyer; Kalkum, Markus; Stajich, Jason E.; Torok, Tamas; Wang, Clay C. C.; Venkateswaran, Kasthuri (Frontiers in Microbiology, 2022)
Due to immense phenotypic plasticity and adaptability, Aspergillus niger is a cosmopolitan fungus that thrives in versatile environments, including the International Space Station (ISS). This is the first report of genomic, proteomic and metabolomic alterations observed in A. niger strain JSC-093350089 grown in a controlled experiment aboard the ISS. Whole genome sequencing (WGS) revealed that ISS conditions, including microgravity and enhanced irradiation, triggered mutations in specific regions, chromosomes VIII and XII of the JSC-093350089 genome when compared to the ground-grown control. Proteome analysis showed altered abundance of proteins involved in carbohydrate metabolism, stress response, and cellular amino acid and protein catabolic processes following growth aboard the ISS. Metabolome analysis further confirmed that space conditions altered molecular suite of ISS-grown JSC-093350089 A. niger. After regrowing both strains on Earth, production of antioxidant - Pyranonigrin A was significantly induced in the ISS-flown, but not the ground control strain. In summary, the microgravity and enhanced irradiation triggered unique molecular responses in the JSC-093350089 A. niger suggesting adaptive responses.